Capacity and Bureaucratic Culture in Accessibility of Public Information Based on E-Government in Sidoarjo-Indonesia - Wahyu Abadi, Totok; Prajarto, Nunung; Guntoro, Budi (United States of America, 2015)
This research is aimed to analyze and describe capacity that included readiness, commitment, and leadership, as well as organizational structure that can affect bureaucratic culture in improving information accessibility based of websites in Sidoarjo Regency. It used mixed methods approach that be done in Sidoarjo Regency with sample of 60 local government employees as respondents and six heads of subdivisions as informants. In addition, it used simple random and purposive sampling with multiple regression analyzing techniques and interactive. The results of this study showed that readiness of bureaucracy in providing access to information via website quite ready. Sidoarjo Regency government has good committed in servicing public information via website. Whereas, leadership, organizational structure, and bureaucratic culture in accessibility of online information quite good. Accessibility of public information based e-government also good (71,01%). Good accessibility of information was driven by openness of public organization active in informing the public whether requested or not; availability of both quantity and quality of information and media that are used to inform and obtain information; ease of use of the media to obtain information quickly, accurately, low cost, easy to understand, and simple procedures; quick for downloading/obtaining information; and comfort in getting/delivering information or interact with government. Simultaneously independent variables such as readiness, commitment, leadership, and organizational structure significantly influence the culture of bureaucracy in providing access to information to the public. Simultaneously, independent variables such as readiness, commitment, leadership, and organizational structure significant towards bureaucracy culture in providing access to public information. The factor that is most influence on the bureaucratic culture in the service of public information accessibility based e-government is leadership and bureaucratic structures. The influence of these two factors is respectively 13.9% and 25% with a power regression by 54.8% and remaining 45.2% are influenced by other factors outside model.